2012
DOI: 10.4414/smw.2012.13575
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac pre-competiton screening in Swiss athletes - Current situation in competitive athletes and short-time assessment of an exemplary local screening program

Abstract: The fact that only 9% of the interviewed competitive athletes had previously undergone cardiac screening is alarming, but underlines the necessity and urgency of implementing a cost-effective and adequate screening concept in the enormous group of competitive athletes who are not integrated in an Olympic- or other high-level squad. The need for a certain self-determination and personal responsibility of the athletes should be respected. Therefore, the screening should not be mandatory. However, adequate inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…4,23 Whether our SrSCD athletes underwent a PPS is unknown; however, it has been suggested that only 9% of non-elite COMP athletes in Switzerland undergo a PPS. 24…”
Section: Discussionmentioning
confidence: 99%
“…4,23 Whether our SrSCD athletes underwent a PPS is unknown; however, it has been suggested that only 9% of non-elite COMP athletes in Switzerland undergo a PPS. 24…”
Section: Discussionmentioning
confidence: 99%
“…In addition to injury prevention, F-MARC has addressed a variety of other medical issues over the years, including, for example, best initial examination to reduce or even prevent sudden cardiac death11 12 environmental influences such as heat13 and altitude14 and the effects of fasting during Ramadan on performance 15 16…”
Section: Fifa (Fédération Internationale De Football Association) Andmentioning
confidence: 99%
“…Open access cardiovascular assessment, has increased over the past two decades, there is little data evaluating athlete experience with the assessment. 9 The available data suggest studentathletes see no value in preparticipation screening and believe the assessment's main role is to prevent injury. In contrast, elite French athletes believe not enough emphasis is placed on injuries.…”
Section: Introductionmentioning
confidence: 99%